Legal education in Spain. A plea - Díez-Picazo, Luis María (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
This text examines, first of all, how law degrees have been declining in public appreciation over the last twenty years. In the author’s view, this has to do with an excess of offer from faculties and centres which are not especially rigorous. Later the text holds that law-teaching for graduate students should be limited to the foundations of basic legal disciplines, even though any serious reform is confronted to the fact that universities are structured upon the idea of «áreas de conocimiento». Lastly the text deals with postgraduate law studies and puts them in connexion to the systems of access to the various legal professions. It stresses some practical difficulties deriving from the fact that a specific master diploma is required to be admitted to the bar.
Keywords: Legal Education; basic legal disciplines; field of knowledge; masters; legal profession